Recurrent neurocysticercosis of the frontal lobe. Case report - Angela Medina Ortega; David López Valencia; Luis Reinel Vásquez Arteaga (Case Reports)
Introduction: Neurocysticercosis (NCC) is the result of ingestion of pork tapeworm eggs (Taenia solium) from an individual with taeniasis (taeniasis/cysticercosis complex). This disease causes the highest helminthic-related morbidity and mortality rates due to its deleterious effects on the central nervous system. 80% of the cases can be asymptomatic and 20% show non-specific clinical manifestations.